Lyotard's agonistic pragmatics: on the problem of legitimacy in postmodernity - Mota, Thiago (Cognitio-Estudos: revista eletrônica de filosofia, 2020)
Where can legitimacy reside in a world in which foundational meta-narratives have fallen apart? To answer this question, we reconstruct the argument that French philosopher Jean-François Lyotard develops in his classic The Postmodern Condition (1979). His proposal is to resume the analysis of language games in terms of a general agonistic, which reveals that the interaction between speech acts constitutes a whole range of power relations. In addition to demonstrating great critical potential, representing the main contribution of that work, Lyotard’s agonistic pragmatics formulates an answer to the problem of legitimation: paralogy, understood as another logic, a logic of difference.